2020
DOI: 10.3390/s20236849
|View full text |Cite
|
Sign up to set email alerts
|

Portable Biosensors for Psychophysiological Stress Monitoring of a Helicopter Crew

Abstract: This study aims to analyze the psychophysiological stress response of a helicopter crew using portable biosensors, and to analyze the psychophysiological stress response differences of experienced and non-experienced crew members. We analyzed 27 participants (33.89 ± 5.93 years) divided into two different flight maneuvers: a crane rescue maneuver: 15 participants (three control and 12 military) and a low-altitude maneuver: 12 participants (five control and seven military). Anxiety, rating of perceived exertion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
(68 reference statements)
0
14
0
Order By: Relevance
“…Regarding the RF articles, 13 were found belonging to this category [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ] and the Venn diagram in Figure 2 shows the trend in the use of the different types of assessing methodologies. The multi-approach is again the most used.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the RF articles, 13 were found belonging to this category [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ] and the Venn diagram in Figure 2 shows the trend in the use of the different types of assessing methodologies. The multi-approach is again the most used.…”
Section: Resultsmentioning
confidence: 99%
“…Pilots must endure a lot of stress during flight emergencies and still be able to give adequate responses to survive and avoid damaging the aircraft. For this reason, the capacity to work under these conditions is essential in this field, as is the ability to safely train and test the pilots [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in the military population and especially in pilots reported an increase in sympathetic activity during flights and combat maneuvers, as well as increased cortical arousal [ 4 , 5 , 7 , 38 , 39 ]. Low HRV typically reflected excessive sympathetic and/or inadequate parasympathetic modulation of heart rate, with reduced HRV observed during periods of emotional and physical stress (behavioral rigidity) and increased HRV during rest [ 4 , 6 , 7 , 37 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in the military field, it was observed that parachute jumping produces a large sympathetic modulation among paratrooper units [ 24 , 25 ], as well as in warfighters in asymmetrical combat environments [ 26 ], underground operations [ 27 ], special operation courses [ 28 ], survival maneuvers [ 29 ], or fighter jet pilots in combat flight maneuvers [ 30 , 31 ] and helicopters crews [ 32 , 33 , 34 ]. Chronic exposure to stressful events in military units was related to the prevalence of anxiety disorders and an increase in diagnoses over time in this millennium, with a prevalence of 0.8 per 100 service members for first service occurrence, followed by post-traumatic stress disorder (PTSD) at a rate of 0.5 out of every 100 [ 35 ].…”
Section: Introductionmentioning
confidence: 99%